Analysis Of Potential Financial Distress Using Altman Z-Score Method : (Study on Companies Listed in the LQ45 Index on the Indonesian Stock Exchange) - Madona, Anggi Siska; Paramitha, Dyah Ayu (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The purpose of this study was to determine the company's financial condition and predict the potential for financial distress in companies listed on the LQ45 Stock Index for the 2020-2022 Period on the Indonesia Stock Exchange using the Altman Z-Score method. Design/Methode/Approach: The approach used in this research is a quantitative approach. The use of a quantitative approach with this descriptive method emphasizes the data processed by the Altman Z-Score method which is measurable, rational and systematic. Research Finding: From the results of data processing, although the companies listed on the LQ45 index have good financial conditions and growth prospects, it is still possible to experience corporate threats. By looking at the company's financial statements, all information regarding the financial position will be known, the company's financial health condition and can be known the performance and changes in the company's financial position which are used for decision making by company stakeholders. Theoretical contribution/Originality: The Altman Z-Score method is a method that can get an estimated accuracy rating of up to 95% and is the most complex method and makes calculations more effective for knowing and predicting potential financial distress. Practitionel/Policy implication: Information obtained from the company's financial statements can be used as a reference to determine the potential for the company's bad condition. So the company can anticipate companies that may experience financial distress. With the Altman Z-Score method that is effective in predicting so that the company can improve the condition of the company so that it can bounce back. Research limitation: More than 45 samples of companies listed in the LQ45 index for the period 2020-2022 which include companies with high levels of liquidity and market capitalization. Research limitations are companies listed in the LQ45 Index that present complete financial reports and data for the 2020-2022 period in accordance with the variables studied.